Kajian Budaya Visual Pasren Dan Transformasi Simbol Kebahagiaan Dan Kemakmuran Pada Masyarakat Modern (Tinjauan Strukturalisme Levi Strauss) - Hesti Rahayu (DeKaVe, 2019)
Abstract.Pasren as a symbol of worship of Dewi Sri in Javanese society, is one of the cultural phenomena. Even though Pasren is no longer well known, even forgotten, but is it true that Pasren is truly extinct, or is it just a form transformation (transformation) both in terms of concept and physical form? This paper tries to answer these questions using Levi-Strauss structural analysis, through the concept of grammar transformation to describe deep structure. The results of the observation show the occurrence of grammar transformation of the concept of happiness and well-being from the existence of KB television and monument in Bantul, Yogyakarta.Keywords: visual-culture,symbol, pasren, structural analysis, grammar-transformation.Relevance to Visual Communication Design Practice: The discussion of visual culture with Levi Strauss's structuralism approach can be an alternative point of view in the research of Visual Communication Design in Indonesia.